Islamic Economics: A Survey of the Literature - Zaman, Asad (Islamic Studies, 2009)
A central thesis of this paper is that social science is the study of human experience, and hence is strongly conditioned by history. Modern Western political, economic and social structures have emerged as a consequence of the repudiation of religion associated with the Enlightenment and are based on secular principles. Many of these are discordant with Islamic principles and cannot be adapted to an Islamic society. Around the middle of the twentieth century Muslim societies successively achieved freedom from colonial rule where-after they sought to construct their collective institutions in conformity with the teachings of Islam. The development of Islamic economics is part of this process of gaining freedom from the stranglehold of Western colonial institutions.This paper is a survey of the literature on Islamic economics which focuses on the contrasts between Western economic theories and Islamic approaches to the organization of economic affairs.